2015
DOI: 10.1590/0001-3765201520140430
|View full text |Cite
|
Sign up to set email alerts
|

Acritarchs of the Ediacaran Frecheirinha Formation, Ubajara Group, Northeastern Brazil

Abstract: We report for the first time the occurrence of organic-walled microfossils in Ediacaran limestones and marls of the Frecheirinha Formation, Ubajara Group, and the first Precambrian acritarchs so far reported for northeastern Brazil. The assemblage of the Frecheirinha Formation represents a low-diversity microflora comprising Leiosphaeridia, Lophosphaeridium and subordinated Bavlinella (=Sphaerocongregus). Sr values between 0.7075 and 0.7080 suggest an Ediacaran age. The acritarch assemblage is comparable to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…23), and the best exposures are observed at the quarry of the Companhia Cearense de Cimento Portland, north of the Aprazível village (Chiglino et al 2015 and references therein). The strata exhibit intense ductile deformation recorded by folds with axes with a NE-SW trend and, locally, low-grade metamorphism.…”
Section: Ubajara Group: Frecheirinha Formationmentioning
confidence: 98%
See 2 more Smart Citations
“…23), and the best exposures are observed at the quarry of the Companhia Cearense de Cimento Portland, north of the Aprazível village (Chiglino et al 2015 and references therein). The strata exhibit intense ductile deformation recorded by folds with axes with a NE-SW trend and, locally, low-grade metamorphism.…”
Section: Ubajara Group: Frecheirinha Formationmentioning
confidence: 98%
“…This metamorphism was probably caused by the intrusion of the nearby Mucambo granite and is not regional in nature. Chiglino et al (2015) selected the Araticum profile, located between the Frecheirinha and Ubajara villages, for palynological study because of the lower thermal overprint. There, limestone-marl rhythmites occur at the base, which pass into dark gray to black, finely laminated, organic-rich limestones, at the top.…”
Section: Ubajara Group: Frecheirinha Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting paper published in this issue of the AABC is on the occurrence of acritarchs from the Precambrian deposits of Northeastern Brazil (Chiglino et al 2015). These organic-walled microfossils are very important not only for dating purposes, but also for potentially providing information about the evolution of eukaryotes (Buick 2010), particularly before the Cambrian Explosion (e.g., Budd 2013).…”
mentioning
confidence: 99%
“…These organic-walled microfossils are very important not only for dating purposes, but also for potentially providing information about the evolution of eukaryotes (Buick 2010), particularly before the Cambrian Explosion (e.g., Budd 2013). Leticia Chiglino and colleagues have found several acritarchs in the Frecheirinha Formation, which is a carbonate deposit of the Ubajara Group (Hackspacher et al 1988 suggested for these deposits which shows a microflora with low diversity, regarded by the authors as not being a taphonomic (preservational) artifact (Chiglino et al 2015). It should be noted that quite recently the first multicellular organisms of the Ediacaran fauna were also reported in Northeastern Brazil, coming from layers that are younger than the Frecheirinha Formation (Barroso et al 2014).…”
mentioning
confidence: 99%